Kinetics Study of Hydrodeoxygenation (HDO) Reaction of Lauric Acid - NIM : 13014001, PATRICK
Along with the growth of the economy and the world population, the need for energy continues to increase. The urgency to use renewable fuels also increases, as fossil fuels will run out of time. Therefore, the development of technology was directed and focused on renewable fuels. One of the renewable fuels studied is bioavtur. Bioavture can be obtained through palm kernel oil. There are several paths that can be passed to obtain bioavtures, and one of the most beneficial pathways is hydrodeoxigenation (HDO). In this research, lauric acid is chosen as the model reactant because lauric acid is the most abundance fatty acid in palm kernel oil. Thus, lauric acid acts as a model compound representing the hydrodeoxigenation reaction of palm kernel oil. The aim of this research is to determine the kinetics equation of HDO lauric acid reaction using NiMo/AIP2 catalyst (developed at Chemical Reaction Engineering Laboratory and Catalysis ITB). This research consisted of kinetics data collection and determination of kinetics equation of HDO reaction. The reaction takes place in a fixed bed continuous reactor with an operating pressure of 50 bar. The temperature variation is around 260-300℃ and LHSV variation is around 0,5-2 h-1. The product of the HDO reaction is then analyzed by gas chromatographic analysis. The results of the analysis can be used to determine reaction conversion and selectivity. The kinetics equation uses Power Law model and can be determined by the ode or Runge-Kutta function in the MATLABÃ‚Â® tool and integration method using Excel. The kinetics equation of HDO reaction obtained follows the first order. Based on the experiment, it is found that the reaction mechanism of lauric acid to dodecanol has an activation energy of 77976 J/mol and Arrhenius value of 6.82E+07/h, and dodecanol to dodecane has an activation energy of 125600 J/mol and Arrhenius value of 4.81E+12/h.